2017
DOI: 10.3389/fphys.2017.00790
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Amelogenin Processing and Changes in Matrix Assembly during Enamel Development

Abstract: The extracellular tooth enamel matrix is a unique, protein-rich environment that provides the structural basis for the growth of long and parallel oriented enamel crystals. Here we have conducted a series of in vivo and in vitro studies to characterize the changes in matrix shape and organization that take place during the transition from ameloblast intravesicular matrices to extracellular subunit compartments and pericrystalline sheath proteins, and correlated these changes with stages of amelogenin matrix pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 65 publications
3
41
0
1
Order By: Relevance
“…Proteomic sex estimation exploits the fact that the highly characterized sex-chromosome-specific amelogenin gene family is expressed as proteins in the most robust tissue in the human body, enamel 33 , 34 , 37 , 58 , 71 . The proteins are cleaved into peptides in situ, as part of enamel formation during tooth biogenesis 50 , 72 , 73 . In order to extract and analyze this peptide population, researchers need to demineralize the enamel and most use acid-based 33 36 , 45 , 46 , 55 , 58 , 74 approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic sex estimation exploits the fact that the highly characterized sex-chromosome-specific amelogenin gene family is expressed as proteins in the most robust tissue in the human body, enamel 33 , 34 , 37 , 58 , 71 . The proteins are cleaved into peptides in situ, as part of enamel formation during tooth biogenesis 50 , 72 , 73 . In order to extract and analyze this peptide population, researchers need to demineralize the enamel and most use acid-based 33 36 , 45 , 46 , 55 , 58 , 74 approaches.…”
Section: Discussionmentioning
confidence: 99%
“…31 This process is based on a polysaccharide/bisphosphonate matrix (chitosan/alendronate) and mimics key steps of initial amelogenesis, including (i) formation of a Ca/P-rich amelogenin protein matrix, (ii) enzymatic degradation and continued crystal growth, and (iii) crystal elongation as facilitated by elongated amelogenin fragments. 32 In their paper, the authors suggested that a combination of non-classical crystallization mechanisms, development of synthetic amelogenin analogues, and imitating remaining biomineralization steps would hold great promise for future approaches to improve the repair of enamel defects. 31…”
Section: Physical Synthesis Approachmentioning
confidence: 99%
“…Once secreted into the extracellular space, amelogenin undergoes a series of proteolytic cleavages starting at the C‐Ame and assemble into nanospheres with a diameter of ≈10–20 nm, which are believed to play a key role in the mineralization and structural organization of enamel. [ 7–9 ] The N‐Ame is crucial for amelogenin self‐assembly into amyloid‐like aggregation through β‐sheet stacking to template the growth of HAp crystals, [ 10,11 ] and the C‐Ame mediate parallel alignment of these crystals [ 12–14 ] ( Scheme ). Hierarchically organized HAp nanorods are further formed in nature involving an aggregation of amorphous calcium phosphate (ACP) nanospheres and a transformation of ACP to HAp crystals (Figure S1, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%